ROOT LENGTH TO WEIGHT RATIO AND WATER USE EFFICIENCY OF PERENNIAL RYEGRASS IN DIFFERENT WATER AND NITROGEN SUPPLIES - Akmal, M.; Asim, M.; Khan, G. D. (The Nucleus, 2020)
Nitrogen, major mineral nutrient for plant growth, often limits the vegetative development and quality of ryegrass Lolium perenne (L). Nitrogen uptake is usually subjected to seasonal moisture availability. The objective of the study was to know response of plant root length to weight ratio (LWR) and water use efficiency (WUE) during early growth, when subjected to varying levels of moisture and N supply. Plants were subjected to low to high water and N levels. Nitrogen was applied @ 9 and 18 g m-2 (N1 and N2) along with 1.5 g P and 4.8 g K m-2. Pots were irrigated uniformly from sowing till 35th day after sowing (440 growing degree days GDD). Thereafter, water supply was restricted to 50 ml day-1 in half of the pots once a week (W1) while the other half received 50 ml pot-1 on daily basis (W2). Destructive samplings were done periodically at weekly interval from 530 growing degree days (GDD) onwards. Leaf weight ratio (LWR) showed a reduction with plants growth until 700 GDD and thereafter, either remained constant or increased slightly after 800 GDD. The decrease in LWR was observed almost at a constant rate for the treatments W1 and W2. Effect of the N treatments on LWR was not prominent (P<0.05) as observed for the water treatments (P<0.01). W1 showed a greater (P<0.01) LWR than W2 in all samplings. A polynomial regression fit best for the LWR when plotted against GDD for all the treatment interactions. Average WUE was higher for N2 than N1 (P<0.05). Water supply levels also showed a significant (P<0.01) response for WUE. The WUE of drought stress plants was observed greater than well irrigated plants. A decrease (P<0.01) in WUE, with plant growth, was observed common for all treatment interactions. The study suggests that limiting N and water supply decreased plant LWR and WUE. Compared to well-watered treatments, drought treatments showed relatively higher LWR as well as WUE of a ryegrass plant.